2D covalent organic framework-based core-shell structures for high-performance solar-driven steam generation. (October 2022) - Xia, Meng; Liang, Ying; Luo, Wenqi; Cai, Dong; Zhao, Peng; Chen, Fanfan; Li, Yongpeng; Sui, Zhuyin; Shan, Linlin; Fan, Ruimei; Pan, Fusheng; Wang, Dong; et al.
Abstract: 2D covalent organic frameworks (COFs) are a promising candidate in the field of solar-driven steam generation (SSG), though their applications are limited by the narrow-band spectral response, complicated framework design, expensive building blocks, and weak chemical stability in current stage. Herein, a composite photothermal material TpPa-COF@MoS2 (MoCOF) with a core-shell structure is prepared by encapsulation of the MoS2 micron-flowers with TpPa-COF via in situ growth to relieve the aforementioned shortcomings. Interestingly, the as-synthesized MoCOF not only presents an enhanced photothermal performance (78.5 °C, at 1 sun intensity) but also has a relative lower cost. Afterwards, a MoCOF@Gel SSG evaporator is fabricated by introducing MoCOF composites into the PVA (polyvinyl alcohol) polymer network. Attributing to the synergistic effects of efficient heat localization, hierarchical water pathways, and hydrophilic channels with a large specific surface area, the MoCOF@Gel shows a high evaporation rate up to 2.31 kg/m 2 /h and energy efficiency of 91.8% under one sun irradiation, which is superior to most of reported COF based steam generators. Furthermore, the MoCOF@Gel also shows robust mechanical property, satisfactory purification performance, and exceptionally antibacterial activity. Graphical abstract: Image 1 Highlights: A COF-based photothermal material prepared by a low-cost preparation process. The MoCOF@Gel shows a robust mechanical property and good hydrophilic performance. An evaporation rate of 2.31 kg/m/h with an efficiency of 91.8% is realized. An excellent antibacterial activity for long-term seawater distillation is achieved.